2004
DOI: 10.1515/jnetdy.2004.012
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on thermodynamical terminology

Abstract: Registration Number 025 Often di‰culties in understanding thermodynamics arise from using di¤erent terminology or semantics. Therefore here some few remarks are made for tending towards a unified thermodynamical terminology. First of all one has to distinguish between two di¤erent description of thermodynamical systems: Such a system can be described as a discrete (or lumped) system or by field formulation. Discrete systems are separated from its environment by partitions. The interaction between the discrete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Meixner's historical remark [23] "... it can be shown that the concept of entropy in the absence of equilibrium is in fact not only questionable but that it cannot even be defined" was the starting-point of a deliberation, if there is a possibility to introduce non-equilibrium entropies which are better founded than a primitive concept. Here, steps are done for a basic substantiation of non-equilibrium entropies for Schottky systems (concerning field formulation see [41,42]). The chain of reasoning is as follows:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meixner's historical remark [23] "... it can be shown that the concept of entropy in the absence of equilibrium is in fact not only questionable but that it cannot even be defined" was the starting-point of a deliberation, if there is a possibility to introduce non-equilibrium entropies which are better founded than a primitive concept. Here, steps are done for a basic substantiation of non-equilibrium entropies for Schottky systems (concerning field formulation see [41,42]). The chain of reasoning is as follows:…”
Section: Discussionmentioning
confidence: 99%
“…vanishing material exchange (41) The quantities 2 ,0 marked by or zero are given thermostatic quantities of several equilibrium environments. The resulting contact quantities of (38) are determined by the following equations: (31) 1,2 and (37).…”
Section: Non-equilibrium Molar Entropiesmentioning
confidence: 99%
“…The entropy identity results by multiplying Equations (5) 1 , (14) and (16) with the present arbitrary quantities κ, λ and Λ c , which are suitably chosen below; Equation (10) 1 becomes:…”
Section: The Entropy Identitymentioning
confidence: 99%
“…The basic ideas of relativistic material theory stem partly from the non-relativistic theory, from the special-relativistic TIP (thermodynamics of irreversible processes) and from general relativity [13][14][15][16][17][18].…”
Section: Appendixmentioning
confidence: 99%
“…Its methods can be successfully applied in various different disciplines such as Physics and Physical Chemistry, Mechanical and Chemical Engineering, Heat and Steam Engine Engineering, Material Science, Bio-Sciences, Energy Conversion Techniques, Air Conditioning and Refrigeration. Consequently, it is impossible to mention the different terminologies [6], methods and schools completely in this brief survey.…”
Section: Introductionmentioning
confidence: 99%